Composition of Cow Milk Kefir Enriched with Ginger Extract (Zingiber officinale) - Putri Dian Wulansari; Novia Rahayu (Universitas Tidar, 2019)
This study aims to analyze the addition of ginger extract (Zingiber officinale) to the composition of cow's milk kefir. Kefir is made from cow's milk with 10% (w/w) kefir grains and ginger extract at intervals of 0, 0.5, 1.0, 1.5 and 2.0% (w/w), all treatments are incubated at room temperature for 24 hours. Kefir composition that was observed was water content, ash content, protein content, and fat content. The results showed that the addition of ginger extract did not affect the composition (water content, ash content, protein content, and fat content) of cow's milk kefir. The average water content, ash content, protein content, and fat content in this study were 90.51%, 5.4%, 3.24%, and 3.18%. The conclusion of this research is the addition of ginger extract to 2% does not affect the composition of cow's milk kefir, but the quality of cow's milk kefir produced meets the standard of kefir composition according to Codex Standard 234-2003. Keywords: Ginger Extract, Kefir, Chemical Composition, Cow Milk